2015
DOI: 10.2147/copd.s80673
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney diseases in patients with chronic obstructive pulmonary disease: assessment based on glomerular filtration rate estimated from creatinine and cystatin C levels

Abstract: BackgroundCardiovascular diseases, osteoporosis, and depression are identified comorbidities of chronic obstructive pulmonary disease (COPD), but there have been few reports of chronic kidney disease (CKD) as a comorbidity of COPD. The objective of this study was to investigate the prevalence of CKD in COPD patients using estimated glomerular filtration rate (eGFR) based on creatinine (Cr) and cystatin C (Cys) levels.MethodsThe prevalence of CKD and the values of various CKD-related parameters were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
2
33
0
7
Order By: Relevance
“…After detailed review of the articles, our literature search resulted in 17 studies related to the topic of our research. Manual search for related articles helped identify an additional study that was recently published and did not have a PubMed ID [17]. Another study was published in April 2016 while we were in the process of submission for publication [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After detailed review of the articles, our literature search resulted in 17 studies related to the topic of our research. Manual search for related articles helped identify an additional study that was recently published and did not have a PubMed ID [17]. Another study was published in April 2016 while we were in the process of submission for publication [18].…”
Section: Resultsmentioning
confidence: 99%
“…Nine of these studies reported the prevalence of CKD in patients with COPD compared to those without COPD [1726]. We reported a detailed review of these studies with data extraction in Table 1 and we included the results reported in these studies in a meta-analysis to estimate the cumulative effect.…”
Section: Resultsmentioning
confidence: 99%
“…2 Indeed, patients with COPD exhibit reduced muscle mass 12 ; thus, the serum creatinine levels might be falsely low as the result of decreased creatine release. 6 This decrease was verified by Yoshizawa et al, 20 who found that the estimated glomerular filtration rate did not differ between the COPD and non-COPD groups when an estimation formula based on serum creatinine was used, but the COPD group exhibited significantly reduced estimated glomerular filtration rate when a formula based on serum cystatin C was employed.…”
Section: Discussionmentioning
confidence: 66%
“…Так, по данным T. Yoshizawa и соавт., при обследовании 108 больных со стабильной ХОБЛ и 79 пациентов без бронхолегоч ных заболеваний было найдено, что уровень креати нина в сыворотке крови был достоверно выше у боль ных с бронхиальной обструкцией, но соотношение СКФ к уровню сывороточного креатинина достоверно между группами не различалось [13]. Более чувстви тельным маркером нарушения фильтрационной функ ции почек при ХОБЛ стал показатель концентрации цистатина С в крови, который был достоверно выше при бронхиальной обструкции, чем при нормальной функции бронхов, а также соотношение СКФ к уровню концентрации цистатина С в сыворотке крови, значе ние которого было значительно ниже в группе боль ных ХОБЛ.…”
Section: Discussionunclassified